2017
DOI: 10.1080/02673843.2017.1292926
|View full text |Cite
|
Sign up to set email alerts
|

The difference in emotional intelligence in relation to levels of maltreatment of Jordanian secondary school students

Abstract: The purpose of this study is to examine the relationship between maltreatment (psychological and neglect) and emotional intelligence among 163 Jordanian students in seventh grade. Two measurements were applied: The Maltreatment and Neglect Scale and The BarOn Quotient Inventory scale. The study results revealed a statistically significant inverse relationship between emotional intelligence and maltreatment. Students subjected to high levels of maltreatment scored lower means in emotional intelligence, and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…Adults who were emotionally abused as a child tend to be emotionally unstable and unresponsive (Rohner and Rohner 1980). In a recent study, psychologically maltreated seventh grade students reported lower scores on interpersonal skills, stress management, and adaptability components of emotional intelligence (Mattar 2018). Moreover, adverse childhood experiences were indirectly associated with aggression via post-traumatic stress disorder only among those who had lower emotional self-regulation (Swopes et al 2013).…”
Section: The Mediating Role Of Trait Emotional Intelligencementioning
confidence: 98%
“…Adults who were emotionally abused as a child tend to be emotionally unstable and unresponsive (Rohner and Rohner 1980). In a recent study, psychologically maltreated seventh grade students reported lower scores on interpersonal skills, stress management, and adaptability components of emotional intelligence (Mattar 2018). Moreover, adverse childhood experiences were indirectly associated with aggression via post-traumatic stress disorder only among those who had lower emotional self-regulation (Swopes et al 2013).…”
Section: The Mediating Role Of Trait Emotional Intelligencementioning
confidence: 98%
“…Previous studies have found that childhood maltreatment can negatively affect social emotions (17), as well as the ability to assess, regulate, and appropriately use emotions, which may lead to a negative impact on emotional intelligence (18, 19). Emotional intelligence is the ability of people to monitor the emotions of themselves and other people, guiding their thoughts and behaviors by discriminating and using information about emotions (20).…”
Section: Introductionmentioning
confidence: 99%
“…The studyfurther identified dysfunctional families, irresponsible parenting, and absence of parents and parents' pressure on adolescents to perform academically as another contributor to learner's suicidal behaviors. Mattar (2018) did a study on the difference in emotional intelligence in relation to levels of maltreatment of Jordanian secondary school students. The study noted a statistically significant inverse relationship between emotional intelligence and maltreatment.…”
Section: Introductionmentioning
confidence: 99%